Semiotics of political-judicial discourse: the confirmation hearing of ex President Laurent Gbagbo in The Hague - ADJUE , Anonkpo Julien; N’Goran , Axel Damauh (Revue Internationale du Chercheur, 2025)
Abstract : Appearing in front of an international court of justice implies speaking out, which requires a strategic approach, especially for a former president of a republic. Verbal communication and non-verbal communication play a significant role in this politico-judicial discourse. The aim of this article is to analyze the discursive strategy employed by the former president during the confirmation of charges hearing in the case against Laurent Gbagbo, in The Hague. More specifically, the article analyzes conscious communication in the manifest content of the speech, unconscious communication in the form of vocal pauses and hesitations in the speech, and body language in the form of hand and head gestures, not forgetting laughter and smiles. As all these elements refer to the rhetorical and argumentative strategy in a speech, it is appropriate to increase the internal validity of the study, using Elan 6.9 software, https://archive.mpi.nl/tla/elan/download. This tool yielded results that could be classified into categories that the authors call triverbal (verbal, paraverbal and non-verbal), also known as the association of modalities enabling the creation of discourse meaning, the end result of which is to influence listeners’ decisions.